The Mineralization of Molluscan Shells: Some Unsolved Problems and Special Considerations - Huang, Jingliang; Zhang, Rongqing (Frontiers in Marine Science, 2022)
The field of biomineralization is an inspiration for human design across disciplines, e.g. biomimetic materials, environmental and biomedical treatments, etc. Having a coherent understanding of the basic science sets the pillars for these fields that will impact human welfare. Intensive studies lead to great progress in unraveling the molecular mechanism underlying molluscan shell formation, especially in the past three decades. However, some problems remain, and discrepancy exists in varied studies. In this review, we pay attention to some issues which have been overlooked and warranted more in-depth studies, and pointed out that considerations should be seriously taken when looking into the cellular and molecular events in shell formation. We first consider the evolution of shell mineralogy and organic matrix by emphasizing the great impact of sea water chemistry. Secondly, we discussed the recent progress on the shell matrix protein (SMP) characterization and pointed out environmental and physiological conditions should be taken into account when studying the SMP functions. Finally, we highlighted some ambiguous issues in the less studied mineralizing tissues and cells, and the underlying cellular control on shell formation. New researchers in this field should keep in mind that early geochemistry in vitro research has mostly failed to address the in vivo context of biomineralization in cells and tissues. Therefore, the more biologically relevant experiments are still needed for future research.